The FTAA and the financial services in the Caribbean : issues and prospects - Henry, Lester (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Examines some of the critical issues facing the financial service sector in the Caribbean in the context of the Free Trade Area of the Americas